KEWENANGAN MAHKAMAH KONSTITUSI DALAM MENGADILI PERKARA PERSELISIHAN HASIL PEMILIHAN KEPALA DAERAH (SUATU KAJIAN TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 97/PUU-XI/2013 JO. PUTUSAN MAHKAMAH KONSTITUSI NOMOR 072-073/PUU-II/2004) - Hardy Salim; Cut Memi (Jurnal Hukum Adigama, 2018)
Acccording to the Arrticle 24C paragaaph (1) the Constttution of thr Republic of Indonesia of 1945, the Constitutional Court of thr Republic of Indonesia have thr power to decide upon disputes over the results of general election. The general election referred to here is elections to elect members of the legislature, regional representative councils, regional legislatures, president amd vice president. Both of thr provisions have been limitative, so there will no be any other elections that included. However, in its development, the Constittutional Court of the Republc of Indonesia is given the power to decide upon disputes ovrr the results of regional hed elections with a legal basis of the Constittutional Court Ruling Number 072-073/PUU-II/2004. However, a litle later the Constttution Court of the Republic of Indonesia issued a Consttttuional Court Ruling Number 97/PUU-XI/2013 which said tht the Constitusional Court of the Republic of Indonesia can’t have the power to decide upon disputes over the resuls of regional hed elections. This reaises problems regarding whether regional head elections are included in thr general election regime? And whether the Constitutional Court of the Republic Indonesia has thr authorty to decide upon disputes over the results of regional hed elections? Thr Author examined the issue by normative method. The results of thr resrarch show tht thr regional hesd elections is not a part of the general electiins regime and the Constututional Corrt of the Republic Indonesia can’t have thr power to decide upon disputes ovrr thr resulls of the regional hesd elections.